DNA Barcoding Evaluation and Its Taxonomic Implications in the Recently Evolved Genus Oberonia Lindl. (Orchidaceae) in China - Li, Yuling; Tong, Yi; Xing, Fuwu (Frontiers in Plant Science, 2016)
The orchid genus Oberonia Lindl., is a taxonomically complex genus characterized by recent species radiations and many closely related species. All Oberonia species are under conservation as listed in the CITES and the IUCN Red List Categories and Criteria. Given its difficulties in taxonomy and conservation status, Oberonia is an excellent model for developing DNA barcodes. Three analytical methods and five DNA barcoding regions (rbcL, matK, trnH-psbA, ITS and ITS2) were evaluated on 127 individuals representing 40 species and 1 variety of Oberonia from China. All the three plastid candidates tested (rbcL, matK and trnH-psbA) have a lower discriminatory power than the nuclear regions (ITS and ITS2), and ITS had the highest resolution rate (82.14%). Two to four combinations of these gene sets were not better than the ITS alone, but when considering modes of inheritance, rbcL+ITS and matK+ITS were the best barcodes for identifying Oberonia species. Furthermore, the present barcoding system has many new insights in the current Oberonia taxonomy, such as correcting species identification, resolving taxonomic uncertainties, and the underlying presence of new or cryptic species in a genus with a complex speciation history.